2015
DOI: 10.1080/07315724.2015.1058197
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study of the Relationship Between Habitual Tea Consumption and Arterial Stiffness

Abstract: Habitual tea consumption may have a protective effect against arterial stiffness, especially for subjects who have habitually consumed tea for more than 6 years and >10 g daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The tested daily doses ranged from 250 to 1200 mg of green tea extract or from 170 to 850 mg of EGCG [143]. Moreover, green tea is associated with an improvement in FMD [144] and pulse wave velocity (PWV) [145], despite no apparent effect on hs-CRP levels [146]. Therefore, overall the consumption of green tea might be associated with a decreased risk of CVD morbidity and mortality [147].…”
Section: Green Tea Extractsmentioning
confidence: 99%
“…The tested daily doses ranged from 250 to 1200 mg of green tea extract or from 170 to 850 mg of EGCG [143]. Moreover, green tea is associated with an improvement in FMD [144] and pulse wave velocity (PWV) [145], despite no apparent effect on hs-CRP levels [146]. Therefore, overall the consumption of green tea might be associated with a decreased risk of CVD morbidity and mortality [147].…”
Section: Green Tea Extractsmentioning
confidence: 99%
“…Therefore, improvement in arterial elasticity is another mechanism for prevention of hypertension. To explore the relationship between habitual tea consumption and arterial stiffness, Lin et al [37] performed a cross-sectional, epidemiological survey of 6,589 male and female residents aged 40–75 years, in Wuyishan, Fujian Province, China. The results showed that the levels of brachial-ankle pulse wave velocity (ba-PWV) were lowest amongst subjects who consumed tea habitually for more than 10 years, compared with the other 3 subgroups (nonhabitual, 1–5 year, and 6–10 year habitual tea drinkers).…”
Section: Tea Regulating Blood Pressure In Human Intervention Studiesmentioning
confidence: 99%
“…Further potentiation of these chemo‐protective properties can occur when the gut interacts with a colonic microbiome and metabolic conversion to smaller more potent phenolic substances than their parent compounds occur 24 . The molecular attributes of these cellular proteins and signalling pathways influence other downstream pleiotropic effects such as decreased arterial stiffness, 25 reductions in LDL cholesterol, 26 lower insulin resistance, improved glycemic control, and a lower risk of metabolic syndrome and diabetes mellitus 19 . Although transient increases in blood pressure following short‐term administration of coffee has been noted, 27 it has not translated to a long‐term risk for hypertension 28 .…”
Section: Discussionmentioning
confidence: 99%